The Task-Based Approach to Teaching Critical Thinking for Computer Science Students - Elena Mäkiö; Juho Mäkiö (MDPI AG, 2023)
Critical thinking (CT) is one of the most important 21st-century skills that employers believe will grow in prominence. However, many higher education (HE) graduates often lack it. This is also true for graduates in computer science (CS) and related disciplines, who need CT to drive social and organizational digitalization. There are a number of strategies for teaching CT. However, there is no evidence regarding how to effectively teach CT in CS. To address this gap, this study proposes an educational approach that aims to promote CT to the students of CS and related disciplines. An educational experiment using this approach was conducted in two modules with similar content. The written reflections of 11 students on their development in CT and the quantitative data of students' self-assessments of their CT skills and dispositions before (N = 20) and after (N = 11) the experiment were analyzed. Priority was given to the qualitative data. The results of this study support the hypothesis that the proposed approach has a positive impact on the development of students' perceived CT skills. They also show that this approach stimulates and promotes students' ability to transfer CT to other tasks and domains and to other contexts and situations. However, the positive development of students' CT dispositions could not be demonstrated in this study, which can be explained by the short duration of this intervention.